Impact of Extreme Drought on Waterbird Abundance: A Case Study Based on the Core Nature Reserve and Surrounding Wetlands - Lei Feng; Jiawei Shi; Yaqin Xiao; Lingjuan Liao; Zongze Zhou; Jialuan Xu; Youzhi Li; Yuxin Tian; Yandong Niu (Ecology and Evolution)
ABSTRACT Wetlands, highly biodiverse yet fragile ecosystems, play vital roles in sustaining waterbird survival and breeding. This study evaluated the impacts of extreme drought on waterbird populations in Dongting Lake and surrounding wetlands by analyzing land use, vegetation, and human disturbance. From 2022 to 2024, three synchronous surveys of wintering waterbirds were conducted in Dongting Lake and its surrounding wetlands to gather habitat information. The results indicated that waterbirds tended to disperse to surrounding wetlands following extreme drought in 2023. In 2023, the waterbird population in the managed lakes was higher than that in the four protected areas of Dongting Lake, whereas in 2022 and 2024, the protected areas maintained larger waterbird populations. The redundancy analysis (RDA) results showed that the temperature vegetation drought index (TVDI; characterizing the degree of drought) and the modified normalized difference water index (MNDWI; characterizing the distribution of water bodies) were the most important factors influencing the distribution of all waterbird populations. Not all dietary groups of waterbirds showed a positive correlation with the MNDWI in terms of population size, but they exhibited a negative correlation with the TVDI. Meanwhile, habitat quality, food availability, and human disturbance were also important factors affecting the population size of all waterbird species. Waterbirds with different diets exhibited variations in the factors, such as food availability, foraging environment, and human disturbance, impacting their foraging behavior and habitat use. Our study suggested that, following a drought, waterbirds dispersed to surrounding wetlands outside the core nature reserve to cope with the negative impact of drought on habitat suitability. However, not all waterbirds with different diets showed dispersal, reflecting different response patterns to drought due to varying feeding habits and foraging methods. Our findings help better understand waterbirds' responses to extreme drought, which is crucial for wetland management and biodiversity conservation.